Introduction to Managerial Accounting - Jackson, Steve
With its easy-to-understand presentation and hands-on learning approach, "Managerial Accounting: A Focus On Ethical Decision Making" gives you everything you need to know as you face the challenges and rewards of the business world. The authors use realistic companies and real issues to clearly illustrate concepts without getting into complex, extraneous data that can be confusing. An innovative and easy-to-learn four-step problem-solving methodology gives you a proven decision-making framework that will help you define the problem, identify the objectives, analyze available options, and select the best solution